Patient Characteristics, Diagnostic Delays, Treatment Patterns, Treatment Outcomes, Comorbidities, and Treatment Costs of Acromegaly in China: A Nationwide Study - Guo, Xiaopeng; Wang, Kailu; Yu, Siyue; Gao, Lu; Wang, Zihao; Zhu, Huijuan; Xing, Bing; Zhang, Shuyang; Dong, Dong (Frontiers in Endocrinology, 2020)
Purpose Acromegaly is a rare, intractable endocrine disease. We aimed to describe the patient characteristics, diagnostic delays, treatment patterns, treatment outcomes, comorbidities and treatment costs of acromegaly in China. Methods This is a nationwide cross-sectional study. Patients diagnosed with and treated for acromegaly between 1996 and 2019 across China were surveyed via the Chinese Association of Patients with Acromegaly platform. Results In total, 473 patients (58.8% females, mean age at diagnosis: 39.4±9.5 years) were included. The median disease duration was 3 years. The most common symptoms were extremity enlargement (91.8%) and facial changes (90.1%). Overall, 63.0% of patients experienced diagnostic delays within healthcare systems; 63.8% of the delays were <1 year. The most common first-line therapy was surgery with a transsphenoidal (76.1%) or transcranial approach (3.2%). Somatostatin analogues or dopamine agonists were administered in 20.5% of the patients as first-line therapies and in 41.7% as adjuvant therapies. Radiotherapy was performed in 32.1% of patients, 99.3% of whom received radiotherapy as an adjuvant therapy. After a median 5-year follow-up, 46.2% achieved biochemical control. Comorbidities were reported in 88.2% of the patients at follow-up; memory deterioration and thyroid nodules were the most common. Controlled patients had greater improvements in symptoms and comorbidities during follow-up than uncontrolled patients. The annual per-capita cost-of-treatment was 11013 in 2018, with medical treatments being the largest contributor (67%). Medical insurance covered 47.2% of all treatment costs. Conclusion This study provides the first comprehensive description of real-world acromegaly data in China, serving as a basis for future population-based studies.